Gaya Komunikasi Pemimpin dan Kinerja Pegawai - Robyan E. Bafadal (Universitas 45 Surabaya, 2024)
Villages are one of the important administrative areas in nation building. There is an expression that building a village means building the nation. Development in the village relies on the work of the Village Head and village officials. Therefore, the Village Head as a leader in the village must be able to embrace the village apparatus. For this reason, the right communication style is needed to embrace the village apparatus. The Village Head must be able to adjust the communication style to the work at hand. By using qualitative data collection techniques, especially in-depth interviews, this paper finds that there is an influence on the communication style of leaders and the performance of village officials as employees. A free and equal communication style is then able to improve employee performance better.